110 The Results of Treatment of Acute Appendicitis During COVID-19 Pandemic in A District General Hospital. (4th May 2021) - Urbonas, T; Centea, D; Wild, T; Thomas, P
Abstract: Aim: At the beginning of the Covid-19 pandemic conservative management of acute appendicitis (AA) was advised to reduce the risk the spread of infection during aerosol generating procedures. The aim of this study was to audit the outcomes of the management of AA in a district general hospital during the pandemic. Method: The prospective data was collected for all patients treated for AA from 12/03/2020 to 18/05/2020. The primary objective was the failure rate of conservative management requiring surgical intervention. Statistical analysis was performed using JASP software. Results: There were 22 patients included. 19 (86%) were managed conservatively of which 4 (21%) patients failed and progressed to surgery and 3 (14%) patients had appendicectomy on admission. 3 patients (20%) treated non-operatively were readmitted within median 4 days (4-6); 2 (13%) of them developed appendix mass. None of the patients had positive SARS-CoV-2 test. Median length of stay (LOS) was 3.5 (1-8) days; 4 (3-8) days in the immediate appendicectomy group, 3 (1-7) in the group managed conservatively. Conclusions: The sample size was small hence it is difficult to draw any solid conclusions. We feel that appendicectomy should remain standard treatment for AA. However, antibiotics should be considered as the first line during the pandemic.